IMPACT OF PREGNANT MARE SERUM GONADOTROPIN (PMSG)INJECTION ON SOME HISTOLOGICAL AND PHYSIOLOGICALPROPERTIES OF AGED JAPANESE QUAIL OVARIES AND TESTES. - الصالحي خالد جلاب كريدي (University of Thi-Qar Journal of Science, 2013)
The present study was conducted at Agriculture and Experimental Research station- Agriculture College - Basrah University to investigate the effect of PMSG administration on some histological and physiological traits of aged Japanese quail (Coturnix japonica). Seventy- two, 10 months old birds of Japanese quail were divided into 3 treatment groups with 2 replicates (6 females and 6 males in each replicate). birds of 1st group were injected once with 100 IU while 2nd group were given 50 IU /bird and 3rd group was considered as control (without injection) , Results revealed that 1st and 2nd groups had a significant (p< 0.05) improvement in histological and physiological characteristics of both ovaries and testes . Ovarian weights of treated groups were significantly (p<0.05) higher than those of 3rd group, while no such differences were exist between relative weight of testes of studied groups. From the present study, it can be concluded that PMSG hormone injection (in both treated groups), improved the histological and physiological characteristics of Japanese quail ovaries and testes.